AUTONOMOUS MACHINING SYSTEMS - Tran, Ngoc-Hien (Vietnam Journal of Science and Technology, 2017)
Intelligent machining systems enable to adapt to the changes of manufacturing environment such as orders, disturbances happening in the system. In machining system, machine tools play an important role to have the products with high quality, low cost and high productivity. The paper presents a new concept of intelligent machining system, namely Autonomous Machining System- AMS. Biology inspired technologies are applied to the machine tools for equipping these machines with biological characteristics such as self-diagnostic, self-recovery, and cooperation. With these advanced characteristics, AMS has ability to adapt to changes on the shop floor.